The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/prs.0000000000003691
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Black Box: The Evidence for the U.S. Food and Drug Administration Warning about the Risk of General Anesthesia in Children Younger than 3 Years

Abstract: On December 14, 2016, the U.S. Food and Drug Administration issued a Drug Safety Communication warning "that repeated or lengthy use of general anesthetic and sedation drugs during surgeries or procedures in children younger than 3 years or in pregnant women during their third trimester may affect the development of children's brains." Health care professionals were urged to "balance the benefits of appropriate anesthesia in young children and pregnant women against the potential risks, especially for procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…FODO's shorter operative time, even with addition of the second procedure for device removal, represents an advantage given the recent trend towards decreasing anesthetic exposure during the first several years of life. 12 It was also associated with less estimated blood loss, and lower blood product transfusion with a trend toward a decrease in hospital stay. Fronto-orbital distraction osteogenesis mediated reconstruction allows surgery to be performed at an earlier age which may be beneficial in order to ameliorate issues associated with increased intracranial pressure, including the poorly understood effects it may have on neuropsychological outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…FODO's shorter operative time, even with addition of the second procedure for device removal, represents an advantage given the recent trend towards decreasing anesthetic exposure during the first several years of life. 12 It was also associated with less estimated blood loss, and lower blood product transfusion with a trend toward a decrease in hospital stay. Fronto-orbital distraction osteogenesis mediated reconstruction allows surgery to be performed at an earlier age which may be beneficial in order to ameliorate issues associated with increased intracranial pressure, including the poorly understood effects it may have on neuropsychological outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…The data presented in this study supports a favorable perioperative profile for the correction of UCS with both treatment modalities. FODO's shorter operative time, even with addition of the second procedure for device removal, represents an advantage given the recent trend towards decreasing anesthetic exposure during the first several years of life 12 . It was also associated with less estimated blood loss, and lower blood product transfusion with a trend toward a decrease in hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1990s, different studies correlating anesthetics with neurotoxicity and neurocognitive sequelae in animal models have been carried out. 13 Data obtained in animal and in vitro studies showed that under experimental conditions, all general anesthetics, including γ-aminobutyric acid agonists and N-methyl-D-aspartate antagonists, have immediate neuroanatomical consequences, 14 such as apoptotic neurodegeneration. 15 However, extrapolating animal research results to humans is still a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with syndactyly usually require surgical intervention at an early age, and much is discussed about the potential implications of exposure to anesthetic agents in childhood. Since the late 1990s, different studies correlating anesthetics with neurotoxicity and neurocognitive sequelae in animal models have been carried out 13 . Data obtained in animal and in vitro studies showed that under experimental conditions, all general anesthetics, including γ-aminobutyric acid agonists and N -methyl- d -aspartate antagonists, have immediate neuroanatomical consequences, 14 such as apoptotic neurodegeneration 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have focused on the development of less invasive tools to evaluate esophagus inflammation, since upper endoscopy is an invasive and expensive procedure, even requiring general anesthesia in children and conscious sedation in most adult patients. Moreover, in 2016, the Food and Drug Administration issued a safety warning states that “repeated or lengthy use of general anesthetic and sedation drugs during surgeries or procedures in children younger than 3 years or in pregnant women during their third trimester may affect the development of children’s brains”, caused increase concerns over anesthetic exposure at a young age leading to anesthetic-induced neurotoxicity [ 99 , 100 ]. Since then, more caution has been used to do repeated EGD under anesthesia.…”
Section: Diagnosismentioning
confidence: 99%